2023
DOI: 10.1186/s12872-023-03150-w
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of elevated blood pressure in abdominal obesity correspond to primary hypertension: a cross-sectional study

Abstract: Background Obesity-related hypertension and the associated metabolic abnormalities are considered as a distinct hypertensive phenotype. Here we examined how abdominal fat content, as judged by waist:height ratio, influenced blood pressure and hemodynamic profile in normotensive subjects and never-treated hypertensive patients. Methods The 541 participants (20–72 years) underwent physical examination and laboratory analyses and were divided into age… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…In a complementary way, abdominal obesity can play a fundamental role in CDV prevention [19]. A recent cross-sectional study found that abdominal fat content was linked with higher blood pressure and arterial stiffness [24]. In this sense, it has been indicated that abdominal obesity was associated with systolic blood pressure and other cardiovascular risk factors [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a complementary way, abdominal obesity can play a fundamental role in CDV prevention [19]. A recent cross-sectional study found that abdominal fat content was linked with higher blood pressure and arterial stiffness [24]. In this sense, it has been indicated that abdominal obesity was associated with systolic blood pressure and other cardiovascular risk factors [24].…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-sectional study found that abdominal fat content was linked with higher blood pressure and arterial stiffness [24]. In this sense, it has been indicated that abdominal obesity was associated with systolic blood pressure and other cardiovascular risk factors [24]. A systematic review of prospective cohort studies reported that the risk of hypertension increased with the elevation of abdominal obesity (i.e., the relative risk of hypertension 1.49 for 10 cm increments in abdominal obesity) [25].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fatty liver can drive hypertension through the development of insulin resistance, dyslipidemia, oxidative stress, and systemic inflammation [ 21 , 23 , 27 , 30 , 39 , 43 , 44 , 45 ]. Obesity-associated hypertension is characterized by systemic vascular resistance and arterial stiffness and seems to represent a distinct clinical phenotype accounting for up to two-thirds of the risk for human essential hypertension [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%